Peran Motivasi Guru PAI dalam Peningkatan Kedisiplinan Siswa di SD Al-Husainiyyah Bandung - Lina Erliana; Helmi Aziz; Sobar Al Ghazal (UNISBA Press, 2022)
Abstract. Islamic education is one of the basic sciences that plays an important role in shaping the character of the mindset and behavior of students. Initial observations made at SD Al-Husainiyyah Bandung became the basis that it turned out that there were several problems with regard to student discipline. The reality showed a tendency such as some students not doing homework or assignments. Therefore PAI teachers or classroom teachers are required to motivate students in discipline and encourage children to apply disciplined attitudes. Based on this phenomenon, the problem in this research is formulated